Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fendo.2020.623038
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Melatonin Increases During Pregnancy and Falls Immediately After Delivery Implicating the Placenta as a Major Source of Melatonin

Abstract: Melatonin is a neuroendocrine hormone which regulates circadian rhythm and is also an antioxidant. The role of melatonin in pregnancy is emerging. The enzymes needed for endogenous synthesis of melatonin have been identified in the placenta, although the contribution to circulating maternal melatonin in normal pregnancy is unclear. This work aimed to determine serum levels of melatonin and its major metabolite 6-hydroxymelatonin sulfate (6-OHMS) in normal pregnant women during each trimester of pregnancy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
1
23
2
Order By: Relevance
“…However, maternal blood and placenta melatonin concentrations of women are variable. Some authors report higher hormone concentration in the blood (Ejaz et al, 2021) and tissue (Lanoix et al, 2012), while others show lower levels (Bouchlariotou et al, 2014) similar to those valours found in blood and placenta in this study and colostrum (Morceli et al, 2013) from diabetic mothers.…”
Section: Discussionsupporting
confidence: 90%
“…However, maternal blood and placenta melatonin concentrations of women are variable. Some authors report higher hormone concentration in the blood (Ejaz et al, 2021) and tissue (Lanoix et al, 2012), while others show lower levels (Bouchlariotou et al, 2014) similar to those valours found in blood and placenta in this study and colostrum (Morceli et al, 2013) from diabetic mothers.…”
Section: Discussionsupporting
confidence: 90%
“…This endogenous synthesis of melatonin diminished with aging and made elderly patient more susceptible to infections or others inflammatory and neurodegenerative diseases 30 , 31 . Other life circumstances may modify this phenomenon like pregnancy 32 . Therefore, future research are needed to explore which innate and environmental factors influence this synthesis, the role of endogenous melatonin in the neonatal brain protection and the potential interaction with exogenous melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin was originally identified as a hormone released from the pineal gland at night but not during the day and was known as the “dark hormone” that promoted sleep 46 . Melatonin is now known to be synthesized and released, but not in a circadian rhythm, from other tissues such as retina, bone marrow, gastrointestinal tract, and placenta 47–49 . When ingested by humans, it is regarded as having a good safety profile established over the last 50 years 50,51 .…”
Section: Therapeutic Options For Activating Nrf2 In “Long Covid” Subj...mentioning
confidence: 99%